Arginine and Polyamines Fate in Leishmania Infection - Muxel, Sandra M.; Aoki, Juliana I.; Fernandes, Juliane C. R.; Laranjeira-Silva, Maria F.; Zampieri, Ricardo A.; Acuña, Stephanie M.; Müller, Karl E.; Vanderlinde, Rubia H.; Floeter-Winter, Lucile M. (Frontiers in Microbiology, 2018)
Leishmania is a protozoan parasite that alternates its life cycle between the sand fly and the mammalian host macrophages, involving several environmental changes. The parasite responds to these changes by promoting a rapid metabolic adaptation through cellular signaling modifications that lead to transcriptional and post-transcriptional gene expression regulation and morphological modifications. Molecular approaches such as gene expression regulation, next-generation sequencing (NGS), microRNA (miRNA) expression profiling, in cell Western blot analyses and enzymatic activity profiling, have been used to characterize the infection of murine BALB/c and C57BL/6 macrophages, as well as the human monocytic cell-lineage THP-1, with Leishmania amazonensis wild type (La-WT) or arginase knockout (La-arg-). These models are being used to elucidate physiological roles of arginine and polyamines pathways and the importance of arginase for the establishment of the infection. In this review, we will describe the main aspects of Leishmania-host interaction, focusing on the arginine and polyamines pathways and pointing to possible targets to be used for prognosis and/or in the control of the infection. The parasite enzymes, arginase and nitric oxide synthase-like, have essential roles in the parasite survival and in the maintenance of infection. On the other hand, in mammalian macrophages, defense mechanisms are activated inducing alterations in the mRNA, miRNA and enzymatic profiles that lead to the control of infection. Furthermore, the genetic background of both parasite and host are also important to define the fate of infection.